A selection of popular literature of oral tradition in the world of Terra de Montes (II) - Troitiño López, Mª José (Madrygal. Revista de Estudios Gallegos, 2014)
This article attempts to compile a selection of lullabies, recitations, elementary games, stories, riddles, etc., collected in Terra de Montes. This entire corpus forms what is known as popular literature of oral tradition; a cultural treasure aimed at children from early to third childhood, encompassing ages from zero to eleven. This is a way of satisfying the appetite for innate knowledge that is consolidated through language, games, stories, etc. In short, this is a selection of games which attempts to set children on their way on the exciting journey of life.
Keywords: dialectology; oral tradition; childhood.